Relevansi Pendidikan Islam Berbasis Ilmu Sosial Profetik Terhadap Pengembangan Kurikulum 2013 di Madrasah - Tatag Satria Praja; Muslih Muslih (Mudir : Jurnal Manajemen Pendidikan, 2021)
Islamic education is not just a process of inculcating moral values to fortify negative access, but how the instilled moral values are able to play a role as the strength of Islam to get out of poverty, ignorance, social and cultural backwardness. Today, the current of modernization gives birth to a culture that leads to liberalization, rationalization, and materialization. This article is a literature review that tries to explore the socio-cultural values that are integrated in the realm of Islamic education that are inseparable from one another. So that Islamic education can adapt and adopt local cultural values of course that do not conflict with the essence of Islamic teachings, so that Islamic education can be easily accepted and grounded in the reality of the society where Islamic education is taught. Islamic education using culture is needed as part of forming the identity of a Muslim. Prophetic social science is an alternative choice of Islamic culture format introduced by Kuntowijoyo through three domains, humanization (amar maruf), liberation (nahyi mungkar), and transcendence, related to the word of Allah Q.S. li-Imran 3:110. Related to these interests, changes are also needed in the National Education System related to the curriculum, in this case the 2013 curriculum in madrasah.